Identification of the contribution of contact and aerial biomechanical parameters in acrobatic performance - Haering, D.; Huchez, A.; Barbier, F.; Holvoët, P.; Begon, M. (PLOS ONE, 2017)
Introduction: Teaching acrobatic skills with a minimal amount of repetition is a major challenge for coaches. Biomechanical, statistical or computer simulation tools can help them identify the most determinant factors of performance. Release parameters, change in moment of inertia and segmental momentum transfers were identified in the prediction of acrobatics success. The purpose of the present study was to evaluate the relative contribution of these parameters in performance throughout expertise or optimisation based improvements. The counter movement forward in flight (CMFIF) was chosen for its intrinsic dichotomy between the accessibility of its attempt and complexity of its mastery.